Areas with abandoned and vacant properties in Croatia a plea for recognition, research, policies and the development of regeneration strategies - Lončar, Sanja, etnologinja; Pavić, Dario (2020)
This paper explores the phenomenon of areas with a large number of abandoned and vacant properties that have a significant impact on the life of communities in economic, environmental and socio-cultural terms. Although the phenomenon has been present in some parts of Europe and the USA for a number of decades, it has become more prevalent in recent decades. The aim of this paper is to explore whether the phenomenon of abandonment is present in contemporary Croatia, as a complex network of negative demographic, social, economic and environmental causes and impacts. Furthermore, the aim is to create a theoretical framework for research into areas with a large number of abandoned or vacant properties in Croatia. Quantitative analyses of key indicators, content analysis of published media and official documents, and ethnographic field research show that abandoned areas are certainly present in Croatia, as are local initiatives to mitigate the negative situation. The recognition of this phenomenon at national, regional and local level needs to be accompanied by the development of an interdisciplinary research methodology, policies and regeneration strategies. Some guidelines on these matters are provided at the end of the paper.
U radu se istražuje fenomen područja s velikim brojem napuštenih i praznih nekretnina koja značajno utječu na život zajednica u ekonomskom, okolišnom i socio-kulturnom smislu. Premda je taj fenomen prisutan u nekim dijelovima Europe i SAD-a već niz desetljeća, posljednjih desetljeća bilježi se njegovo jačanje. Cilj je ovog rada istražiti je li fenomen napuštenosti prisutan u suvremenoj Hrvatskoj kao složena mreža negativnih demografskih, socijalnih, ekonomskih i okolišnih uzroka i utjecaja. Nadalje, cilj je stvoriti teorijski okvir za istraživanje područja s velikim brojem napuštenih ili praznih nekretnina u Hrvatskoj. Kvantitativne analize ključnih pokazatelja, analiza medijskih sadržaja i službenih dokumenata te etnografska terenska istraživanja pokazuju da su napuštena područja zasigurno prisutna u Hrvatskoj, a isto tako i lokalne inicijative za ublažavanje negativne situacije. Prepoznavanje tog fenomena na nacionalnoj, regionalnoj i lokalnoj razini treba pratiti razvoj interdisciplinarnih istraživačkih metodologija, politika i strategija regeneracije. Neke smjernice o tim pitanjima iznose se na kraju rada.
Bibliografske bilješke uz tekst ; bibliografija: str. 227-237.
Summary ; Sažetak.
Keywords: Napuštene nekretnine -- Deprivacija -- Blagostanje -- Regeneracija; Hrvatska